Marine streptomyces SP. UKMCC_PT15 producing undecylprodigiosin with algicidal activity - Zainal Abidin, Zaima Azira; Ahmad, Asmat; Latip, Jalifah; Usup, Gires (UTM, 2016)
Marine actinomycetes are now in demand as they are capable of producing unique and novel compounds with wide biological activities. Marine Streptomyces sp. UKMCC_PT15 previously isolated from seawater collected in Pulau Tinggi, Johor was used in this study. Molecular identification showed high similarity of Streptomyces sp. UKMCC_PT15 with Streptomyces fradiae and S. diastaticus subsp. ardesiacus based on partial sequence of 16S rRNA gene. Further characterisations of this bacterium include spore morphology using SEM, growth on various media, salt tolerance test and carbon utilisation profile. This bacterium had straight spore chain with smooth-surfaced spores and was able to tolerate up to 11% NaCl with capabilities of utilising >40 carbon sources. Undecylprodigiosin (C25H35N3O) was successfully purified through succession of column chromatography and finally using HPLC. Structure elucidation was confirmed through NMR spectroscopy, MS and comparison with established data. This compound demonstrated strong antibacterial activities against S. aureus, B. subtilis and C. albicans but weak antibacterial activities against E. coli, P. aeruginosa and Methicillin-resistant S. aureus (MRSA), Interestingly, undecylprodigiosin also demonstrated algicidal activity when tested against toxic dinoflagellates, A. minutum and P. bahamense, both of which are responsible for harmful algal blooms (HABs). Undecylprodiogiosin with concentration of 10-100 μg/ml gave ~100% algicidal activity against both dinoflagellates. Further testing with undecylprodigiosin concentration < 10 µg/ml showed that undecylprodigision was capable of killing significantly high numbers of both dinoflagellates, giving a high algicidal activity. Findings from this study suggested the potential use of undecylprodigiosin as algicidal agent which could be used for the mitigation of HABs.